Trend analysis of carbapenem-resistant Gram-negative bacteria and antimicrobial consumption in the post-COVID-19 era: an extra challenge for healthcare institutions. (February 2022) - de Carvalho Hessel Dias, V.M.; Tuon, F.; de Jesus Capelo, P.; Telles, J.P.; Fortaleza, C.M.C.B.; Pellegrino Baena, C.
Summary: The incidence density trend of the carbapenem-resistant Gram-negative bacteria was analysed in device-associated infections and antimicrobial consumption in 99 critical care facilities in a low/middle-income country, between January 2019 and December 2020. Carbapenem-resistant Acinetobacter baumannii (CRAB) per 1000 patient-days increased in 2020 and this finding had a strong positive correlation with the incidence density of COVID-19 by the Spearman test. Polymyxin consumption also increased in 2020 but without significant correlation with CRAB or COVID-19 incidence density, presumably due to empirical and untargeted prescribing as a consequence of concern about CRAB infections. These findings are a warning to infection control programmes and antimicrobial stewardship.